Improving the performance of bioelectrochemical sulfate removal by applying flow mode. Issue 3 (19th October 2022) - Dai, Shixiang; Harnisch, Falk; Bin‐Hudari, Mohammad Sufian; Keller, Nina Sophie; Vogt, Carsten; Korth, Benjamin
Abstract: Treatment of wastewater contaminated with high sulfate concentrations is an environmental imperative lacking a sustainable and environmental friendly technological solution. Microbial electrochemical technology (MET) represents a promising approach for sulfate reduction. In MET, a cathode is introduced as inexhaustible electron source for promoting sulfate reduction via direct or mediated electron transfer. So far, this is mainly studied in batch mode representing straightforward and easy‐to‐use systems, but their practical implementation seems unlikely, as treatment capacities are limited. Here, we investigated bioelectrochemical sulfate reduction in flow mode and achieved removal efficiencies ( E sulfate, 89.2 ± 0.4%) being comparable to batch experiments, while sulfate removal rates ( R sulfate, 3.1 ± 0.2 mmol L −1 ) and Coulombic efficiencies ( CE, 85.2 ± 17.7%) were significantly increased. Different temperatures and hydraulic retention times (HRT) were applied and the best performance was achieved at HRT 3.5 days and 30°C. Microbial community analysis based on amplicon sequencing demonstrated that sulfate reduction was mainly performed by prokaryotes belonging to the genera Desulfomicrobium, Desulfovibrio, and Desulfococcus, indicating that hydrogenotrophic and heterotrophic sulfate reduction occurred by utilizing cathodically produced H2 or acetate produced by homoacetogens ( Acetobacterium ). The advantage of flow operation for bioelectrochemical sulfate reduction is likely based on higher absolute biomass, stable pH, and selection of sulfate reducers with a higher sulfide tolerance, and improved ratio between sulfate‐reducing prokaryotes and homoacetogens. Abstract : In this study, continuous mode was applied to initial autotrophic bioelectrochemical sulfate reduction allowing a tripling of the sulfate removal rate compared to batch mode conditions which had been applied in previous studies. Microbial community analysis demonstrated the presence of a few hydrogenotrophic and heterotrophic sulfate reducers but also an increased abundance of homoacetogens, a process which is seemingly beneficial for bioelectrochemical sulfate reduction as the produced acetate could lead to an improved biomass production.